Pembelajaran dan Pemerolehan Bahasa: Prinsip Perbedaan dan Faktor Pendukungnya dalam Pendidikan Formal - Mauluddiya Saniyatul Iskaq; Endah Rahmawati; Jihan Sunniyah Syakuroh Ni'mah; M. Yunus Abu Bakar (Moral : Jurnal kajian Pendidikan Islam, 2026)
This article aims to systenatically examine the concepts of language learning and language acquistionwithin thw context of formal education. The discussion begins with an explanationof the principles of learning and language intuctrion that serve as the theoretical fundationfor the language mastery procces. These principles encompass cognitive, affective and social aspect that are interconnected in shaping student’ language competence.  Furthemor, the article describes the differences in language learning characteristics between childern and adults, viewed form cognitive development, level of motivation, and learning strategies osed in comprehending and producing language. In addition, the study highlist the conceptual distimction between language acquistion and language learning. Language acquisition occurs naturally through interaction and exposure in daily communication, whereas language  learning is a planed and systematic process that generaly takes place in formal educational settings. The article aslo analyzes  supporting factors that contribute to the succes of both processes, including internal factors such as motivation, interest, and individual abilities, as well as external factors such as learning environmen, teaching methods, intructuional media, and social support. Understanding these aspects is expected tpo provide a basis for designing effective language instruction aligned with learnes’ characteristics.